A The Challenges and Solutions of Implementing Differentiated Instruction in Islamic Religious Education at Private Madrasah Tsanawiyah in the Poso Kota Bersaudara District - Makmur Makmur; Nurqadriani; Harpina; Uswatun Hasanah; M. N Jamalia (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
This study aims to identify the challenges and solutions in implementing differentiated learning in Islamic Religious Education (PAI) subjects at private Madrasah Tsanawiyah (MTs) in the Poso Kota Bersaudara District. A descriptive qualitative approach was employed, with data collected through in-depth interviews, classroom observations, and document analysis. The research subjects consisted of six PAI subject teachers from three MTs: MTs Alkhairaat Poso, MTs Muhammadiyah Poso, and MTs Al-Ikhlas Sayo. The findings revealed that teachers face various challenges in applying differentiated learning, including lack of curriculum training, classroom management difficulties, diverse student characteristics, and limited instructional resources and media. Solutions implemented include ongoing training, professional development, more personalized and varied instructional approaches, more efficient time management, and increased creativity in utilizing digital learning media. The study concludes that despite persistent challenges, adaptive and innovative strategies can enhance the effectiveness of differentiated instruction and positively impact student participation, motivation, and learning outcomes in Islamic Religious Education.